Brittle bone disease - A rare genetic disorder: A case report - Goyal, Suresh; Meena, Pradeep; Mehrotra, Juhi; Malvia, Sunny; Rawat, Ravi; Meena, Mahendra; Dodiyar, Roshani (Indian Journal of Child Health, 2018)
Osteogenesis imperfecta (OI) is a group of rare inherited disorders of connective tissue with the hallmark of excessive fragility of bones caused by mutations in collagen characterized by remarkable soft and large cranium and short-curved limbs. Radiological findings, such as, under mineralization of skull, platyspondyly, severely short and deformed long bones, and small continuously beaded ribs, pathognomonic for OI, were observed. Considering the clinical/radiological manifestations, a diagnosis of OI was made.